STIMULUS-ORGANISM-RESPONSE (S-O-R) MODEL APPLICATION IN EXAMINING THE INFLUENCE OF SOCIAL MEDIA MARKETING ON PURCHASE DECISIONS IN THE HEALTHCARE INDUSTRY: THE MEDIATING ROLE OF BRAND TRUST - Vidyanata, Deandra (Universitas Brawijaya, Indonesia, 2022)
Social media has revolutionized the traditional marketing paradigm, where traditional marketing communication is usually regarded as a one-way relationship between service providers and consumers. The purchase decision is the final stage of a complex consumer decision-making process. which can be influenced by various marketing stimulus, one of which is Social Media Marketing activities. Heretofore, there is no certainty regarding the extent to which the effectiveness of Social Media Marketing affects purchase decisions, especially in the healthcare industry. This study employs The Stimulus-Organism-Response (S-O-R) Model to explain the role of Brand Trust (O) in mediating the influence of Social Media Marketing activities (S) on Purchase Decision (R) in the healthcare industry. The sampling technique used in this study is purposive sampling. The results of this study show that Social Media Marketing cannot directly affect purchase decisions. However, Social Marketing is proven effective in generating Brand Trust, which evokes consumers' purchase decisions. Furthermore, Brand Trust is found to be a full mediation in effect between Social Media Marketing on purchase decisions. Thus this study substantiates the implication of the Stimulus-Organism-Respons Model in the healthcare industry.